2013
DOI: 10.1111/bjd.12371
|View full text |Cite
|
Sign up to set email alerts
|

Psychological differences between early- and late-onset psoriasis: a study of personality traits, anxiety and depression in psoriasis

Abstract: Our results indicate that early detection of psychological vulnerability when treating children and adolescents with psoriasis seems to be of great importance. Traits of psychological vulnerability and pessimistic personality traits were found to be significantly associated with the early onset of psoriasis, but not with disease duration in this study. These traits may be seen as a consequence of psoriasis, and/or as individual traits modulating and impairing clinical course and efforts to cope with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
5
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 40 publications
2
52
5
5
Order By: Relevance
“…On the other hand, they have shown that limited psoriasis on a visible area may also have greater impact on mental health (21) . Recently, a study from Sweden showed that early detection of psychological vulnerability when treating patients with psoriasis seems to be of great importance (22). They showed a significant relationship between early onset disease and grater psychological symptoms and concluded that these traits may be seen as a consequence of psoriasis, and/or as individual traits modulating and impairing clinical course and efforts to cope with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they have shown that limited psoriasis on a visible area may also have greater impact on mental health (21) . Recently, a study from Sweden showed that early detection of psychological vulnerability when treating patients with psoriasis seems to be of great importance (22). They showed a significant relationship between early onset disease and grater psychological symptoms and concluded that these traits may be seen as a consequence of psoriasis, and/or as individual traits modulating and impairing clinical course and efforts to cope with psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…De Jager et al [14] interviewed 15 pediatric psoriasis patients (mean age 12.8 ± 4.25 years), 65% of whom felt stigmatized due to bullying or name calling. The stigmatization and bullying lead to a decreased perception of social connectivity that impacts family and social relationships [18] . Adolescents with psoriasis have expressed feelings of isolation and being 'different than others', with some families even planning vacations that revolved around the adolescent's comfort and ability to keep lesions concealed [16] .…”
Section: Hrql In Adolescents With Chronic Illness and Psoriasismentioning
confidence: 99%
“…In fact, increased anger levels frequently accompanying psychiatric disorders has been also studied in patients with psoriasis and increasing level of anger was noted in several studies [13,14]. It was found that anxiety, insecurity and aggressive behaviors were more common especially in patients with early-onset psoriasis [5,10,[14][15][16]. However, the correlation of anger and anger expression styles with self-esteem in psoriasis which is a psychosomatic disease has not been studied before.…”
Section: Introductionmentioning
confidence: 99%